Correlation between clean and healthy lifestyle behavior of mother with the incident of diarrhea in toddlers at working area of Puskesmas I Negara, Jembrana - Bali - Sharrmila Rajan Inderan; Wayan Weta (DiscoverSys Inc., 2018)
Background: Diarrhea defines as the increase of defecation frequency more than usual, which is more than three times per day, accompanied by the change of feces’ consistency become way waterier with or without blood and mucus. Risk factors that can cause diarrhea included the transmission of bacteria, immune deficiency from the host increases the vulnerable towards diarrhea and environment factor along behavior. The combination of unhealthy environmental factors because of tainted diarrhea bacteria and bad human behavior was the main cause of diarrhea. This research aims to know the correlation between clean and healthy lifestyle behavior of mother with the incidents of diarrhea in toddlers.Methods: This research is an analytic study with cross-sectional approach. The data of this study were collected through questionnaire. The data were analyzed by univariate and bivariate.Results: 50 samples were included in this study with 58% aged 20-30 years old. Bivariate analysis showed that clean and healthy lifestyle behavior category of mother, washing hand, and toilet usage were correlated with the incidence of diarrhea in toddlers with PR (p-value) consecutively 1,9 (p=0.028); 3.9 (p=0.004); and 6.25 (p=0.002).Conclusions: Majority of respondents have bad clean and healthy lifestyle behavior (CHLB) category, and the incidence of diarrhea in toddler tends to be more in mothers with bad clean and healthy lifestyle behavior (CHLB) category.